Nano zinc oxide dispersion for polyester in-situ polymerization and preparation method thereof

By adding nano zinc oxide dispersion in the ethylene glycol system online during the polyester synthesis process, the problem of large amount of addition and uneven distribution in masterbatch technology is solved, and the uniform distribution of nano zinc oxide in polyester and the performance of polyester is improved, which is suitable for large-scale industrial production.

CN116355280BActive Publication Date: 2025-04-04ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310173599.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-04-04
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

In the prior art, when nano zinc oxide is added to polyester, the masterbatch technology has problems such as large amount of addition, uneven distribution, high cost and high energy consumption, and is not suitable for large-scale industrial production.

Method used

The reactant ethylene glycol during polyester synthesis is used as a modification system for nano zinc oxide. The nano zinc oxide is surface treated by compound modifiers to make a stable dispersion of ethylene glycol system. It can be added online during the polyester synthesis process to improve the dispersion of nano powders and polyester properties.

Benefits of technology

It realizes uniform distribution of nano zinc oxide in polyester, improves the performance of polyester, reduces production costs and energy consumption, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004100032930000061
    Figure BDA0004100032930000061
  • Figure BDA0004100032930000071
    Figure BDA0004100032930000071
Patent Text Reader

Abstract

The invention discloses a nano zinc oxide dispersion for polyester in-situ polymerization and a preparation method thereof, the components of which include: nano zinc oxide, ethylene glycol, a compound modifier, a stabilizer and a dispersant; the compound modifier includes a long carbon chain coupling agent and a coupling agent containing a reactive group; the long carbon chain coupling agent contains at least one alkyl chain of C6 or more; the coupling agent containing a reactive group contains one or more of an amino group, an epoxy group and a thiol group. The invention uses a compound modifier to perform surface treatment on nano zinc oxide to prepare a stable dispersion of an ethylene glycol system, which can be added online in the pulping or esterification section of the polyester synthesis process, greatly improving the dispersibility of nano powders and improving polyester performance, without special equipment expenditure, and is convenient for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester additives, in particular to a nano zinc oxide dispersion for polyester in-situ polymerization and a preparation method thereof. Background Art

[0002] Adding antibacterial nanopowders to polyester fibers is one of the most effective methods for developing antibacterial polyester fibers. Nano zinc oxide has a broad spectrum and high efficiency antibacterial property, and has photocatalytic antibacterial, active oxide antibacterial, and metal ion dissolution antibacterial properties. It has a killing rate of 99% for Escherichia coli, Staphylococcus aureus and other bacteria, and has anti-ultraviolet properties. It is an excellent nano additive. Adding zinc oxide to polyester materials to prepare antibacterial polyester fibers has been widely used.

[0003] Since inorganic nanoparticles have a special surface structure and lack adjacent coordinating atoms on their surface, they are highly active and easily agglomerated; and the compatibility of inorganic particles with polyester matrix is ​​poor, so they cannot be directly blended with polyester materials for melt spinning. In the prior art, nano zinc oxide is added to polyester mostly by masterbatch technology, first making a nano powder functional masterbatch, and then blending with polyester for melt spinning. For example, a "method for manufacturing inorganic nano zinc oxide multifunctional composite antibacterial polyester fiber" disclosed in Chinese patent literature, with publication number CN102560725A, first prepares hydrophilic modified polyester chips, blends zinc oxide powder below 100 nanometers with fiber-forming polymer at a weight ratio of 20-35:80-65, and then processes it into a masterbatch suitable for polyester fiber production through a special process. The specially prepared masterbatch is blended with hydrophilic modified polyester chips at a weight percentage of 5% to 15%, and is made into inorganic nano zinc oxide multifunctional composite antibacterial polyester fiber through a polyester fiber production process.

[0004] Although the use of masterbatch technology to add nano zinc oxide is simple and flexible, it has problems such as large amount of masterbatch added, uneven distribution of nano zinc oxide, short cycle of slice spinning components, high cost and high energy consumption, and is not suitable for large-scale industrial production. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned problems existing in the prior art of adding nano zinc oxide using masterbatch technology, and provides a nano zinc oxide dispersion for polyester in-situ polymerization and a preparation method thereof. The nano zinc oxide is surface treated with a compound modifier to prepare a stable dispersion of an ethylene glycol system, which can be added online in the pulping or esterification stage of the polyester synthesis process, greatly improving the dispersibility of the nano powder and improving the polyester performance. No special equipment expenditure is required, and industrial production is convenient.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A nano zinc oxide dispersion for polyester in-situ polymerization comprises: nano zinc oxide, ethylene glycol, a compound modifier, a stabilizer and a dispersant; the compound modifier comprises a long carbon chain coupling agent and a coupling agent containing a reactive group; the long carbon chain coupling agent contains at least one alkyl chain of C6 or above; the coupling agent containing a reactive group contains one or more of an amino group, an epoxy group and a thiol group.

[0008] The present invention selects ethylene glycol, a reactant in polyester synthesis, as the solvent of the nano zinc oxide dispersion, and does not require the operation steps of removing the solvent such as centrifugation, spraying, or suction filtration in the conventional nano powder modification process, thereby greatly reducing the modification difficulty of the nano zinc oxide; the prepared nano zinc oxide dispersion is easy to use, has no special requirements for polymerization, and can be directly added in the pulping or esterification stage in the polyester synthesis process.

[0009] At the same time, the present invention uses a composite modifier to modify the nano zinc oxide, and the composite modifier contains two different coupling agents. The long carbon chain coupling agent can change the surface of the nano zinc oxide from hydrophilic to hydrophobic, thereby improving the compatibility of the nano zinc oxide with the polyester matrix; the amino group, epoxy group and thiol group in the coupling agent containing a reactive group can react with the carboxyl group in the reactant during polyester synthesis, so that the nano zinc oxide can be connected to the polyester matrix through a chemical bond, which is beneficial to improving the performance of the polyester. In addition, the long carbon chain coupling agent and the coupling agent containing a reactive group can work together to adjust the zinc oxide particle size in the dispersion to a suitable range, so that the nano zinc oxide can be stably dispersed in ethylene glycol, so that the nano zinc oxide in the polyester obtained by polymerization can be evenly distributed.

[0010] Preferably, in the compound modifier, the mass ratio of the long carbon chain coupling agent and the coupling agent containing the reactive group is 0.2 to 5:1; the total mass of the compound modifier is 0.5 to 5% of the mass of the nano zinc oxide. By controlling the amount of the long carbon chain coupling agent and the coupling agent containing the reactive group within this range, the particle size in the dispersion can be adjusted to the optimal range to ensure that the dispersion has good dispersion stability. If the amount of the long carbon chain coupling agent is too small, the coverage of zinc oxide is incomplete and the particle size is large; when the amount of the long carbon chain coupling agent is too large, the excess organic long chains are entangled with each other, which also causes the particle size to become larger. If the amount of the coupling agent containing the reactive group is too small, the nano zinc oxide cannot participate in the synthesis reaction of the polyester, the zinc oxide cannot be evenly distributed in the polyester, and the strength of the polyester decreases; and when the amount of the coupling agent containing the reactive group is too large, the polyester will be severely cross-linked, which is not conducive to the later fiber processing.

[0011] Preferably, the long carbon chain coupling agent is selected from one or more of isopropoxy tris(dioctyl pyrophosphate acyloxy) titanate, isopropoxy trioleyl titanate, propoxy titanium tristearate, isopropoxy tris(dodecylbenzenesulfonyloxy) titanate, octadecyl trimethoxy silane, and hexadecyl trimethoxy silane; the coupling agent containing a reactive group is selected from one or more of isopropoxy tris(ethylenediamino-N-ethoxy) titanate, 3-aminopropyl triethoxy silane, N-2-aminoethyl-3-aminopropyl triethoxy silane, 3-glycidyloxypropyl triethoxy silane, and 3-mercaptopropyl triethoxy silane.

[0012] Preferably, the stabilizer is selected from one or more of trimethyl phosphate, triethyl phosphate, triphenyl phosphate, and triethyl phosphoric acid; the mass of the stabilizer is 0.005-0.02% of the mass of nano zinc oxide. The stabilizer in the present invention can reduce the catalytic activity of nano zinc oxide and avoid the degradation of polyester catalyzed by zinc oxide.

[0013] Preferably, the dispersing aid comprises a first dispersing aid and a second dispersing aid; the first dispersing aid is polyethylene glycol (PEG) with a molecular weight lower than 1000 and / or polyvinyl pyrrolidone with a molecular weight greater than 58000; the mass of the first dispersing aid is 0.3-5% of the mass of nano zinc oxide; the second dispersing aid is sodium polyacrylate and / or sodium hexametaphosphate; the mass of the second dispersing aid is 0.25-1% of the mass of nano zinc oxide.

[0014] The adsorption vacancies on the first dispersant can be complexed with the surface of zinc oxide, or form hydrogen bonds, and adsorbed on the surface of zinc oxide, maintaining the size of zinc oxide less than 3 μm for the next step of coupling agent modification, preventing it from being modified in the form of agglomerates and unable to be ground open later. The second dispersant can be adsorbed on the surface of the modified zinc oxide, increasing the surface potential and repulsion, and ensuring the storage stability and thermal stability of the dispersion in the later stage.

[0015] Preferably, the mass concentration of nano zinc oxide in the dispersion is less than 15%.

[0016] The present invention also provides a method for preparing the above-mentioned nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0017] (1) mixing nano zinc oxide with ethylene glycol, adding a dispersant and grinding until the particle size D99 of the zinc oxide is less than 3 μm, to obtain an initial dispersion;

[0018] (2) adjusting the pH of the initial dispersion to 10-12, and adding a composite modifier dropwise to carry out a modification reaction;

[0019] (3) adding a stabilizer and a dispersant to the dispersion after the modification reaction, and grinding again until the particle size of zinc oxide is less than 1 μm to obtain the nano zinc oxide dispersion for in-situ polymerization of polyester.

[0020] Preferably, the dispersant added in step (1) is the first dispersant, and the dispersant added in step (3) is the second dispersant.

[0021] Preferably, the pH adjuster used to adjust the pH in step (2) is one or more of ammonia water, triethanolamine, organic amine, and sodium hydroxide; and the modification reaction temperature is 50 to 120°C.

[0022] Preferably, the particle size of the grinding beads used in step (1) and step (3) is 0.3 to 0.6 μm, and the grinding temperature is lower than 40°C.

[0023] Therefore, the present invention has the following beneficial effects:

[0024] (1) Ethylene glycol, a reactant in polyester synthesis, is selected as the modification system of nano zinc oxide. There is no operation step of removing solvent such as centrifugation, spraying, or filtration in the conventional nano powder modification process, which greatly reduces the modification difficulty of nano zinc oxide. The residual compound modifier is strictly controlled by process conditions. It is easy to use and has no special requirements for polymerization. It can be directly added in the pulping or esterification stage of the polyester synthesis process.

[0025] (2) The nano zinc oxide is modified by two coupling agents of different properties in a strictly controlled ratio, which solves the problem of controlling the particle size of the nano zinc oxide when it is dispersed in the ethylene glycol system, and solves the problem of compatibility and reactivity between the nano zinc oxide and the polyester matrix after polymerization; the nano zinc oxide dispersion has good stability, and the nano zinc oxide can be evenly distributed in the polyester obtained by polymerization; (3) The polyester chips prepared by the dispersion of the present invention can still maintain the excellent properties of the polyester fiber after melt spinning to make the antibacterial polyester fiber, and the spinnable single yarn fineness can be adjusted to a specification of less than 1 dtex through the process. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific implementation methods.

[0027] In the present invention, unless otherwise specified, the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.

[0028] Embodiment 1:

[0029] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0030] (1) 50 g of nano zinc oxide (Aladdin) was mixed with 450 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.4 μm zirconium beads. During the grinding process, 0.45 g of PEG600 was added dropwise until the particle size of D99 was less than 3 μm, thereby obtaining an initial dispersion;

[0031] (2) Transfer the mixture into a flask, adjust the pH value to 10 with aqueous ammonia, raise the temperature to 50°C, dropwise add 0.5 g of 3-aminopropyltriethoxysilane and 0.8 g of isopropoxytrioleyl titanate within 1 hour, keep the mixture warm for 16 hours, and cool naturally;

[0032] (3) The dispersion after the modification reaction in step (2) is transferred to a sand mill, ground with 0.3 μm zirconium beads, and 0.05 g of sodium polyacrylate and 0.05 g of triethyl phosphate are added dropwise to grind until D99 is less than 0.6 μm, thereby obtaining the nano zinc oxide dispersion for in-situ polymerization of polyester.

[0033] Embodiment 2:

[0034] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0035] (1) 50 g of nano zinc oxide (Aladdin) was mixed with 450 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.4 μm zirconium beads. During the grinding process, 0.6 g of PEG600 was added dropwise until the particle size of D99 was less than 2 μm, to obtain an initial dispersion;

[0036] (2) Transfer the mixture into a flask, adjust the pH to 11 with aqueous ammonia, raise the temperature to 80°C, add 1.3 g of 3-aminopropyltriethoxysilane and 1.2 g of octadecyltrimethoxysilane dropwise over 0.5 hours, keep the mixture warm for 6 hours, and cool naturally;

[0037] (3) The dispersion after the modification reaction in step (2) is transferred to a sand mill, ground with 0.3 μm zirconium beads, and 0.25 g of sodium hexametaphosphate and 0.05 g of triethyl phosphate are added dropwise to grind until D99 is less than 0.6 μm, thereby obtaining the nano zinc oxide dispersion for in-situ polymerization of polyester.

[0038] Embodiment 3:

[0039] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0040] (1) 50 g of nano zinc oxide (Aladdin) was mixed with 450 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.4 μm zirconium beads. During the grinding process, 0.6 g of PEG400 was added dropwise until the particle size of D99 was less than 2 μm, to obtain an initial dispersion;

[0041] (2) transferring the mixture into a flask, adjusting the pH value to 10.5 with aqueous ammonia, raising the temperature to 85° C., dropping 1 g of 3-aminopropyltriethoxysilane and 0.5 g of isopropoxytri(dioctylpyrophosphate)titanate within 0.5 hours, keeping the mixture warm for 3 hours, and cooling naturally; (3) transferring the dispersion after the modification reaction in step (2) into a sand mill, grinding the mixture with 0.3 μm zirconium beads, dropping 0.25 g of sodium hexametaphosphate and 0.05 g of triethyl phosphate, and grinding the mixture until the D99 is less than 0.6 μm to obtain the nano zinc oxide dispersion for in-situ polymerization of polyester.

[0042] Embodiment 4:

[0043] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0044] (1) 50 g of nano zinc oxide (Aladdin) was mixed with 450 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.4 μm zirconium beads. During the grinding process, 0.6 g of PEG400 was added dropwise until the particle size of D99 was less than 2 μm, to obtain an initial dispersion;

[0045] (2) transferring the mixture into a flask, adjusting the pH value to 10 with aqueous ammonia, raising the temperature to 85° C., dropping 1 g of 3-aminopropyltriethoxysilane and 0.6 g of isopropoxytri(dodecylbenzenesulfonyloxy)titanate within 0.5 hours, keeping the mixture warm for 4 hours, and cooling naturally; (3) transferring the dispersion after the modification reaction in step (2) into a sand mill, grinding the mixture with 0.3 μm zirconium beads, dropping 0.25 g of sodium hexametaphosphate and 0.1 g of triethyl phosphate, and grinding the mixture until the D99 is less than 0.6 μm to obtain the nano zinc oxide dispersion for in-situ polymerization of polyester.

[0046] Embodiment 5:

[0047] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0048] (1) 25 g of nano zinc oxide (Aladdin) was mixed with 475 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.3 μm zirconium beads. During the grinding process, 0.4 g of PEG400 was added dropwise until the particle size of D99 was less than 1 μm, thereby obtaining an initial dispersion;

[0049] (2) Transfer the mixture into a flask, adjust the pH value to 11 with aqueous ammonia, raise the temperature to 85° C., dropwise add 1 g of 3-glycidyloxypropyltriethoxysilane and 0.5 g of propoxytitanium tristearate within 1 hour, keep the temperature for reaction for 3 hours, and cool naturally;

[0050] (3) Adding 0.05 g of triethyl phosphate to the dispersion after the modification reaction in step (2) can directly obtain the nano zinc oxide dispersion for in-situ polymerization of polyester without secondary grinding.

[0051] Embodiment 6:

[0052] A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester, comprising the following steps:

[0053] (1) 25 g of nano zinc oxide (Aladdin) was mixed with 475 g of ethylene glycol, fully dispersed with a high-speed disperser, and ground with a sand mill loaded with 0.3 μm zirconium beads. During the grinding process, 0.4 g of PEG400 and 0.2 g of PEG1000 were added dropwise until the particle size of D99 was less than 1 μm, thereby obtaining an initial dispersion;

[0054] (2) Transfer the mixture into a flask, adjust the pH to 10.5 with aqueous ammonia, raise the temperature to 70°C, dropwise add 1 g of 3-mercaptopropyltriethoxysilane and 1.3 g of hexadecyltrimethoxysilane within 1 hour, keep the mixture warm for 5 hours, and cool naturally;

[0055] (3) Adding 0.1 g of triethyl phosphate to the dispersion after the modification reaction in step (2) can directly obtain the nano zinc oxide dispersion for in-situ polymerization of polyester without secondary grinding.

[0056] Comparative Example 1 (no coupling agent containing reactive groups is added):

[0057] The difference between Comparative Example 1 and Example 1 is that in step (2), no 3-aminopropyltriethoxysilane is added, and only 0.8 g of isopropoxytrioleyl titanate is added dropwise, and the rest is the same as in Example 1.

[0058] Comparative Example 2 (too much coupling agent containing reactive groups was added):

[0059] The difference between Comparative Example 2 and Example 1 is that in step (2), 5 g of 3-aminopropyltriethoxysilane and 0.8 g of isopropoxytrioleyl titanate are added dropwise, and the rest is the same as in Example 1.

[0060] Comparative Example 3 (without adding long carbon chain coupling agent):

[0061] The difference between Comparative Example 3 and Example 1 is that in step (2), no isopropoxy trioleyl titanate is added, and only 0.5 g of 3-aminopropyl triethoxysilane is added dropwise, and the rest is the same as in Example 1.

[0062] Comparative Example 4 (too much long carbon chain coupling agent added):

[0063] The difference between Comparative Example 4 and Example 1 is that 0.5 g of 3-aminopropyltriethoxysilane and 3 g of isopropoxytrioleyl titanate are added dropwise in step (2), and the rest is the same as in Example 1.

[0064] The dispersions prepared in the above embodiments and comparative examples were subjected to particle size and half-year sedimentation stability analysis, centrifugal washing and hydrophilic and hydrophobic contact angle tests, and made into polyester slices to observe the agglomerated particles and to perform melt filtration performance tests (referring to the new DIN EN 13900-5 Pigments and fillers - Diffusion method and evaluation of diffusibility in plastics and FZT51019-2021 polyester fiber masterbatch). The results are shown in Table 1.

[0065] The preparation method of the polyester chips is as follows: terephthalic acid, ethylene glycol, the nano zinc oxide dispersion obtained by the present invention, and ethylene glycol antimony are added into a 2.5L reactor, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.25 (ethylene glycol contained in the dispersion is calculated in the reactants), the added mass of the nano zinc oxide dispersion is 80g, and the added amount of ethylene glycol antimony is 30ppm; stirring and heating to 240°C, controlling the pressure in the reactor to reach 360kPa, slowly releasing the pressure to discharge water, reacting for 2.5h, and ending the esterification when the esterification rate reaches 95%; starting a vacuum pump for polycondensation, maintaining the pressure in the reactor at 100Pa, and controlling the temperature at 278°C. After reacting for 3h, the polyester melt is discharged through a bottom valve for pelletizing to obtain polyester chips.

[0066] Table 1: Dispersion and polyester chip performance test results.

[0067]

[0068]

[0069] As can be seen from Table 1, by adjusting the ratio of the two coupling agents in the composite modifier, the particle size and contact angle are used as the modification degree of zinc oxide. In Examples 1 to 6, the method of the present invention is adopted, and the D99 particle size of the nano zinc oxide dispersion is less than 1 μm, the dispersion has good placement stability, and no stratification occurs; after modification by the composite coupling agent, the surface of the nano zinc oxide is transformed into a hydrophobic surface, and the contact angle is 97 to 108°. At this time, the nano zinc oxide is well dispersed in the polyester, the melt filtration performance is good, there is no obvious pressure increase, and the fewer the agglomerated particles, the smaller the filter pressure difference.

[0070] In Comparative Example 1, when no coupling agent containing reactive groups was added and only long carbon chain coupling agents were used to modify the nano zinc oxide, the particles were relatively hydrophobic, the particle size was too large, the stability was poor, and they could not be stably dispersed in ethylene glycol. The agglomerated particles in the slices could not be counted, and the pressure increased significantly in the filter press value test. In Comparative Example 2, too much coupling agent containing reactive groups was added, which exceeded the scope of the present invention, resulting in a larger particle size of zinc oxide, and zinc oxide modified with too many reactive groups became crosslinking points, causing serious crosslinking of polyester, obvious agglomeration, and a rapid increase in pressure in the filter press value test.

[0071] In Comparative Example 3, no long carbon chain coupling agent is added, and only a coupling agent containing a reactive group is used to modify the nano zinc oxide. The situation is similar to that in Comparative Example 2. Since no long carbon chain coupling agent is added, the compatibility between zinc oxide and the polyester matrix deteriorates, and the pressure rise is obvious in the filter pressure value test. In Comparative Example 4, too much long carbon chain coupling agent is added, and the excess long carbon chains of the coupling agent are entangled with each other, the zinc oxide is seriously agglomerated, and it is difficult to separate during the polymerization process, and the pressure rise is obvious in the filter pressure value test.

Claims

1. A nano zinc oxide dispersion for polyester in-situ polymerization, characterized in that the components include: Nano zinc oxide, ethylene glycol, compound modifier, stabilizer and dispersant; The compound modifier includes a long carbon chain coupling agent and a coupling agent containing a reactive group; the long carbon chain coupling agent contains at least one alkyl chain of C6 or above; the coupling agent containing a reactive group contains one or more of an amino group, an epoxy group, and a thiol group; In the compound modifier, the mass ratio of the long carbon chain coupling agent to the coupling agent containing the reactive group is 0.2-5:1; the total mass of the compound modifier is 0.5-5% of the mass of the nano zinc oxide.

2. The nano zinc oxide dispersion for polyester in-situ polymerization according to claim 1, characterized in that: The long carbon chain coupling agent is selected from one or more of isopropoxy tris(dioctyl pyrophosphate acyloxy) titanate, isopropoxy trioleyl titanate, propoxy titanium tristearate, isopropoxy tris(dodecylbenzenesulfonyloxy) titanate, octadecyl trimethoxy silane, and hexadecyl trimethoxy silane; The coupling agent containing a reactive group is selected from one or more of isopropoxy tris(ethylenediamino-N-ethoxy) titanate, 3-aminopropyl triethoxy silane, N-2-aminoethyl-3-aminopropyl triethoxy silane, 3-glycidyloxypropyl triethoxy silane, and 3-mercaptopropyl triethoxy silane.

3. The nano zinc oxide dispersion for polyester in-situ polymerization according to claim 1, characterized in that: The stabilizer is selected from one or more of trimethyl phosphate, triethyl phosphate, triphenyl phosphate and triethyl phosphoric acid; the mass of the stabilizer is 0.005-0.02% of the mass of the nano zinc oxide.

4. The nano zinc oxide dispersion for polyester in-situ polymerization according to claim 1, characterized in that: The dispersant comprises a first dispersant and a second dispersant; The first dispersant is polyethylene glycol with a molecular weight lower than 1000 and / or polyvinyl pyrrolidone with a molecular weight greater than 58000; the mass of the first dispersant is 0.3-5% of the mass of nano zinc oxide; The second dispersant is sodium polyacrylate and / or sodium hexametaphosphate; the mass of the second dispersant is 0.25-1% of the mass of nano zinc oxide.

5. The nano zinc oxide dispersion for polyester in-situ polymerization according to claim 1, characterized in that: The mass concentration of nano zinc oxide in the dispersion is less than 15%.

6. A method for preparing a nano zinc oxide dispersion for in-situ polymerization of polyester as claimed in any one of claims 1 to 5, characterized in that: The steps include: (1) Mixing nano zinc oxide with ethylene glycol, adding a dispersant and grinding until the particle size D99 of zinc oxide is less than 3 μm, to obtain an initial dispersion; (2) Adjust the pH of the initial dispersion to 10-12, and add the compound modifier dropwise to carry out the modification reaction; (3) Adding a stabilizer and a dispersant to the dispersion after the modification reaction, grinding again until the particle size of zinc oxide is less than 1 μm, thereby obtaining the nano zinc oxide dispersion for polyester in-situ polymerization.

7. The preparation method according to claim 6, characterized in that: The dispersant added in step (1) is the first dispersant, and the dispersant added in step (3) is the second dispersant.

8. The preparation method according to claim 6, characterized in that: The pH adjusting agent used in step (2) for adjusting the pH is one or more of ammonia water, triethanolamine, organic amine, and sodium hydroxide; and the modification reaction temperature is 50-120°C.

9. The preparation method according to claim 6, characterized in that: The particle size of the grinding beads used in step (1) and step (3) is 0.3-0.6 μm, and the grinding temperature is lower than 40°C.

Citation Information

Patent Citations

  • Production method of inorganic nanometer zinc oxide multifunctional composite antibacterial polyester fiber

    CN102560725A

  • Preparation method of light-colored PET polyester conductive fiber based on conductive zinc oxide

    CN105350107A

  • Metal oxide ink modified by silane coupling agent as well as preparation method and application of metal oxide ink

    CN113831786A